Bank Credit and Economic Growth in Nepal: An Empirical Analysis - Timsina, Neelam (NRB Economic Review, 2014)
This study examines the impact of commercial bank credit to the private sector on the economic growth in Nepal from supply side perspectives. The study has applied Johansen co-integration approach and Error Correction Model using the time series data for the period of 1975-2014. The empirical results show that bank credit to the private sector has positive effects on the economic growth in Nepal only in the long run. Nevertheless, in the short run, it has been observed a feedback effect from economic growth to private sector credit. More specifically, the growth in real private sector credit by 1 percentage point contributes to an increase in real gross domestic product by 0.40 percentage point in the long run. The empirical results imply that, policy makers should focus on long run policies to promote economic growth – development of modern banking sector, efficient financial market and infrastructure so as to increase the private sector credit which is instrumental to promote growth in the long run.